Coastal Community and Youth Knowledge of HIV/AIDS Indonesia: A Review - Jamal Saripa; Hardianto (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: HIV/AIDS remains a significant global health issue, including in Indonesia, which ranks fifth among countries with the highest HIV/AIDS prevalence after South Africa, India, Mozambique, and Nigeria. By 2023, it is estimated that approximately 1.7 million people in Indonesia are living with HIV/AIDS. Coastal communities, particularly fishermen and their families, are considered a vulnerable group due to limited access to health services and lack of health education. Therefore, targeted efforts are essential to prevent HIV/AIDS transmission in these communities, including Voluntary Counseling and Testing (VCT) services and educational interventions to raise awareness about HIV/AIDS. Objective: This study aims to analyze the level of knowledge and awareness regarding HIV/AIDS among coastal communities and adolescents through a literature review. Methods: A qualitative literature review was conducted by collecting and synthesizing findings from previous studies relevant to HIV/AIDS prevention in coastal communities. Results: The literature review highlights the importance of VCT services for early detection and risk assessment of HIV/AIDS in coastal populations. Empowering housewives as health cadres facilitates effective communication and education about HIV/AIDS due to their familiarity with local community dynamics. Outreach programs, including educational lectures and the distribution of informational leaflets, have proven effective in improving the knowledge and attitudes of both adults and adolescents toward HIV/AIDS prevention. Conclusion: Community-based empowerment and cross-sector collaboration are critical to enhancing HIV/AIDS awareness and prevention in coastal areas. Keywords: Coastal Community, Knowledge, Global Health, HIV/AIDS